Kepemimpinan Partisipatif dalam Mewujudkan Sekolah Terakreditasi Unggul (Studi Kasus di SDN Cijaya, Kecamatan Campaka, Purwakarta) - Tatang Permana; Ina Nurmuminah; Suharyanto Soro; Dinny Mardiana (Civiliza Publishing, Indonesia., 2025)
The paradigm shift in school accreditation through the IASP 2024 instrument requires education units to focus not on administrative completeness alone, but on proof of performance and quality culture. The current challenge is that there are still many schools that only focus on the completeness of documents. It requires a leadership style of a school principal who is able to mobilize the full potential of school residents. This research aims to explore participatory leadership in realizing schools with superior accreditation status. This research uses a qualitative paradigm with a case study approach. The data collection method is through observation methods, in-depth interviews, and documentation studies. Samples are selected based on Purposive Sampling. In this case, the respondent/sample taken is the Principal chosen because as the manager and chairman of the KKKS, teachers are selected based on their level of education and class rank. Data analysis used the interactive model Miles, Huberman, and Saldana, and validated through triangulation of sources and techniques. The findings of the study show that (1) Planning is carried out in an inclusive manner by involving teachers, committees, parents, and the village government in the preparation of school programs; (2) This program is carried out through the empowerment and delegation of authority of the accreditation team according to the teacher's competence, so as to build a sense of ownership of the program. (3) Evaluation is characterized by open two-way communication and accountable administrative order and follow-up leads to continuous improvement that has an impact on the achievement of quality standards. It was concluded that participatory leadership at SDN Cijaya was effective following the theoretical foundation.